2010
DOI: 10.1136/emj.2009.085845
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Full Outline of Unresponsiveness (FOUR) Scale for conscious state in the emergency department: comparison against the Glasgow Coma Scale

Abstract: The FOUR Scale showed greater reliability than the GCS in ED patients using ED clinicians as raters. A larger study of ED patients is warranted to determine the predictive validity of the FOUR Scale and to further examine the reliability of the scale in various patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
2
17
1
5
Order By: Relevance
“…It was developed by Wijdicks et al, [4] and further validations of this scale were done by other researches. [5][6][7][8][9][10] It is composed of eye, motor, brainstem, and respiration responses with a scale of 0-4 (0=worst, 4=best) as demonstrated in Table 1. The FOUR score specifically distinguishes certain unconsciousness states, provides important details such as brainstem reflexes, and includes the minimal necessities of neurological testing in altered mental status.…”
Section: Sonuçmentioning
confidence: 99%
“…It was developed by Wijdicks et al, [4] and further validations of this scale were done by other researches. [5][6][7][8][9][10] It is composed of eye, motor, brainstem, and respiration responses with a scale of 0-4 (0=worst, 4=best) as demonstrated in Table 1. The FOUR score specifically distinguishes certain unconsciousness states, provides important details such as brainstem reflexes, and includes the minimal necessities of neurological testing in altered mental status.…”
Section: Sonuçmentioning
confidence: 99%
“…As a result probability of in hospital mortality is higher for the lowest total FOUR score when compared with that of GCS. FOUR score has been subjected to validation studies [11][12][13][14][15][16] in different scenarios like neuro ICU, emergency departments, medical ICU, comatose stroke patients in acute stroke unit , traumatic brain injuries etc. It has been compared with GCS in these validation studies and excellent inter rater agreements have been observed.…”
mentioning
confidence: 99%
“…], and among examiners with different medical backgrounds and levels of experience [7][8][9][10][11][12][13][14][15]. In this issue, Marcati et al properly evaluate the Italian version of the FOUR score in 87 patients with acute brain injuries.…”
mentioning
confidence: 99%
“…The FOUR score would be an ideal scale for evaluating comatose patients, since according to Marcati et al, it has proved to be reliable (measuring what it is supposed to measure), valid (giving similar results with repetition), practical (easy to use after minimum training), and highly accurate as a prognostic indicator (test of accuracy yield even higher positive likelihood ratio values for the FOUR score compared to the GCS) [9]. Recent inter-rater reliability studies demonstrate a better agreement with the use of the FOUR score compared to the GCS among medical examiners (especially neurologists) and a lesser, but still good to excellent agreement among examiners with non-neurological backgrounds (including nurses) [7][8][9][10][11]. This may raise uncertainties whether experience may play a significant role in the use of this scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation